2022
DOI: 10.1007/s40263-022-00955-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychobehavioural and Cognitive Adverse Events of Anti-Seizure Medications for the Treatment of Developmental and Epileptic Encephalopathies

Abstract: The developmental and epileptic encephalopathies encompass a group of rare syndromes characterised by severe drug-resistant epilepsy with onset in childhood and significant neurodevelopmental comorbidities. The latter include intellectual disability, developmental delay, behavioural problems including attention-deficit hyperactivity disorder and autism spectrum disorder, psychiatric problems including anxiety and depression, speech impairment and sleep problems. Classical examples of developmental and epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 304 publications
(440 reference statements)
0
32
0
2
Order By: Relevance
“…However, other AEDs with different mechanisms of action may be more effective in treating other types of seizures, such as those associated with GABA imbalances or calcium channel dysfunction. Additionally, lamotrigine is less likely to cause sedation or cognitive impairment compared to some other anti-epileptic drugs, which makes it effective for the treatment of certain mood disorders in addition to epilepsy [ 44 ].…”
Section: Overview Of Antiepileptic Drugsmentioning
confidence: 99%
“…However, other AEDs with different mechanisms of action may be more effective in treating other types of seizures, such as those associated with GABA imbalances or calcium channel dysfunction. Additionally, lamotrigine is less likely to cause sedation or cognitive impairment compared to some other anti-epileptic drugs, which makes it effective for the treatment of certain mood disorders in addition to epilepsy [ 44 ].…”
Section: Overview Of Antiepileptic Drugsmentioning
confidence: 99%
“…The objectives of treatment for epilepsy-associated comorbidities should focus on the positively controlling seizures, as well as reasonable interventions for comorbidities should be developed that can improve the patients' quality of life ( 4 ). As research progresses, it has been found that ASMs might have different psychiatric or psychological effects on patients, including the psychiatric and behavioral side effects (PBSEs) ( 42 , 43 ). Some ASMs have no cognitive effects on PWE (e.g., gabapentin, and lamotrigine), whereas phenytoin sodium, topiramate, and zonisamide can adversely affect the cognition ( 44 ).…”
Section: Epilepsy-associated Comorbiditiesmentioning
confidence: 99%
“…Отмена препарата в связи с утратой временного эффекта проведена у 8 (7,7 %) пациентов (все пациенты с генетическими эпилептическими энцефалопатиями). В целом в связи с проблемами эффективности препарат отменен у 17 (16,3 %) Безусловно, очень важное значение имеет отсутствие отрицательного влияния ламотриджина (и данные о его потенциально положительном эффекте) на когнитивные функции при ЭРЭ, по данным недавно проведенного обзора литературы, изучающего когнитивные и поведенческие эффекты АЭП именно в популяции пациентов с ЭРЭ [73]. В нашем наблюдении ни в одном из случаев пациентами или их родителями не было отмечено негативного влияния на когнитивные функции и психическую сферу при приеме Сейзара.…”
Section: о р и г и н а л ь н ы е с т а т ь и | O R I G I Nunclassified
“…Приводим обобщающие данные отчета рабочей группы ILAE о действии АЭП на когнитивные функции и поведение детей, основанные на результатах обзора литературы [25]. По данным недавно проведенного обзора литературы по вопросу влияния АЭП на поведение, психическую сферу и когнитивные функции при ЭРЭ [73], леветирацетам, перампанел и, в меньшей степени, бриварацетам ассоциированы с психическими и поведенческими нарушениями (включая агрессивность и раздражительность) у пациентов этой категории. Топирамат и, в меньшей степени, зонисамид ассоциированы с речевыми нарушениями, когнитивной заторможенностью и проблемами памяти, а также с негативным влиянием на ряд аспектов когнитивных функций, в то время как ламотриджин, а также леветирацетам и бриварацетам могут оказывать положительный эффект на когнитивные функции.…”
Section: о р и г и н а л ь н ы е с т а т ь и | O R I G I Nunclassified